Studies on the Weeds Infestation and their Management in Teak Plantations - Clarson, D.; Sudha, P. (Indian Forester, 1997)
The study undertaken in the Teak plantations of Sterling Tree Magnum (I) Ltd., revealed that the grasses like Cynodon sp. And Cyperus sp. Were the dominant weeds occurring in all the plantations. Chemical weeding at the early stages of weed growth with Gramaxone @ 2.5 ml/l + Tritone @ 1 ml/l was found to he effective. In areas heavily infested with grasses Glycel @ 7.5 ml/l was found to he effective. Once the weeds establish themselves and sets flowers, manual/mechanical weeding is the effective method for complete elimination of underground tubers. Based on the labour availability and spacing of trees and the topography of the terrain either manual or mechanical weeding can be resorted to. Thus the weed control practice should involve an integrated practice of chemical weeding, manual weeding and mechanical weeding.